(untitled) (Coordinates of Public Administration, 2025)
The article substantiates the foundations for building the cultural resilience of Ukrainian society as one of the key dimensions of humanitarian security in the context of a full-scale war. It emphasizes that, under crisis conditions, cultural resilience is not only a domain of symbolic self-identification, but also a practical resource for social cohesion, countering destructive information and psychological influences, maintaining public trust, and restoring social ties within communities. The study defines the strategic importance of cultural security within the overall national security system and outlines humanitarian policy priorities relevant to both wartime and post-war periods. These priorities include: harmonizing and integrating humanitarian doctrines and policy documents; developing and protecting cultural infrastructure (cultural institutions, heritage preservation networks, and cultural-educational hubs); and modernizing governance approaches in the cultural sphere by strengthening institutional capacity, transparency, and the effectiveness of resource use. To enable practical application of the core concept of «cultural resilience», the article proposes a working definition that moves it from the level of declarations to measurable indicators and governance planning. An analysis of international initiatives in cultural security and the protection of cultural heritage demonstrates the potential for adapting tested approaches and instruments to the Ukrainian context, taking into account the specific nature of wartime threats, the scale of destruction, and recovery needs. It is argued that the transfer of practices should not occur through mechanical borrowing, but through institutional «re-adaptation», i.e., alignment with the legal framework, administrative capacities, and the real needs of territorial communities.